ANALISIS EFEKTIFITAS STRATEGI PEMASARAN PRODUK KREDIT PENSIUN PADA BANK MANDIRI TASPEN GUNUNGSITOLI - Kristiani Yarniman Daeli; Yupiter Mendrofa; Otanius Laia; Maria Magdalena Batee (Jurnal Publikasi Manajemen Informatika, 2026)
This study aims to analyze the effectiveness of the marketing strategies implemented by Bank Mandiri Taspen Gunungsitoli for its pension credit products and to identify the factors influencing their effectiveness as well as the challenges encountered in their implementation. The study is motivated by the important role of marketing strategies in increasing customers’ interest in and understanding of pension credit products. However, their implementation in practice continues to face several challenges, including low levels of financial literacy, limited promotional media, and inconsistencies between strategic planning and execution. This research employs a descriptive qualitative approach. Data were collected through interviews, observations, and documentation studies. The research informants consisted of the Branch Manager, Pension Account Officers, and Customer Service Officers of Bank Mandiri Taspen Gunungsitoli. The findings indicate that the marketing strategies implemented by Bank Mandiri Taspen Gunungsitoli through the marketing mix elements—product, price, promotion, place, people, process, and physical evidence—have been reasonably effective in reaching pensioner customers. Nevertheless, their effectiveness can be further enhanced through digital marketing innovations, increased direct outreach to pensioner communities, and improved financial literacy among customers.